Menuju Pengembangan Industri Kreatif di Indonesia - Nur Iswantara (Rekam: Jurnal Fotografi, Televisi, Animasi)
Discourse of creative industries was echoed. The government alsodeveloped the concept of creative industries development. Alvin Toffler,the father futuristic was said ideas and creative ideas into the fourthwave that could affect the world economy. Indonesia also inspired thedevelopment of creative industries of the world, adopted the triple helixmodel to drive the creative industries to creative economy towardsIndonesia. There are 14 industry groups developed creative Indonesia.In this position the creative industries need to get a response fromintellectuals and the public.